The Self-Appointed Jury: Punitive Sentiment And Prosocial Aggression In Christie’s Orient Express - Donny Syofyan (Krinok:Jurnal Linguistik Budaya, 2025)
This study presents a biocultural analysis of Agatha Christie’s Murder on the Orient Express (1934) through the theoretical lens of Literary Darwinism. While traditional scholarship often focuses on the novel’s formalist "puzzle-box" structure, this research explores the underlying evolutionary pressures that drive its unconventional resolution. By utilizing key concepts such as inclusive fitness, altruistic punishment, and reciprocal altruism, the article argues that the narrative functions as a cognitive simulation of ancestral justice.The findings reveal that the "Armstrong Circle" operates as a surrogate kinship unit responding to a catastrophic fitness insult—the murder of a child. The collective execution of the predator, Cassetti, is analyzed as a biological correction triggered by an evolved punitive sentiment when formal legal structures fail. Furthermore, the study interprets Hercule Poirot’s final acquittal of the killers as a biocultural compromise, where the detective’s "modular mind" recognizes the validity of proximal biological imperatives over distal social laws. Ultimately, this research suggests that the novel’s enduring global popularity stems from its profound alignment with the fundamental evolutionary heritage and moral intuitions of the human species.Keywords: literary darwinism, inclusive fitness, altruistic punishment, biocultural compromise, cheater detection, fictive kinsh